Profil Kemampuan Berpikir Komputasional (Computational Thinking) Siswa SMP Negeri Se-Kota Semarang Tahun 2022 - Nuvitalia, Duwi; Saptaningrum, Ernawati; Ristanto, Sigit; Putri, M R (Universitas PGRI Semarang, 2022)
This study aims to determine the profile of the mastery of computational thinking skills of State Junior High School students throughout the city of Semarang with the benefit of being a benchmark for innovation or development of learning models oriented to mastering the computational thinking skills of State Junior High School students in the city of Semarang. This research was conducted in 15 public junior high schools in the city of Semarang on March 25, 2022 - April 30, 2022. The sample in the study amounted to 15 public junior high schools from a population of 45 public junior high schools in the city of Semarang. Data were taken using a free test instrument to measure students' computational thinking skills and teacher questionnaires to obtain information related to learning science in schools. The free test is given online via google form and offline using a question sheet. The total respondents were 328 students as the research sample. The result of this research is that the profile of mastery of computational thinking skills of State Junior High School students in Semarang city gets a score of 54.97. Based on the results of the study, it can be concluded that students' computational thinking skills are in the medium category and there are still students who have not been able to solve problems with computational thinking skills, namely abstraction, generalization, pattern recognition, decomposition, and algorithms.Keywords: Computational Thinking, Bebras task, Science Learning for State Junior High Schools of Semarang city